2016
DOI: 10.3390/cells5010013
|View full text |Cite
|
Sign up to set email alerts
|

Src1 is a Protein of the Inner Nuclear Membrane Interacting with the Dictyostelium Lamin NE81

Abstract: The nuclear envelope (NE) consists of the outer and inner nuclear membrane (INM), whereby the latter is bound to the nuclear lamina. Src1 is a Dictyostelium homologue of the helix-extension-helix family of proteins, which also includes the human lamin-binding protein MAN1. Both endogenous Src1 and GFP-Src1 are localized to the NE during the entire cell cycle. Immuno-electron microscopy and light microscopy after differential detergent treatment indicated that Src1 resides in the INM. FRAP experiments with GFP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 53 publications
0
33
0
Order By: Relevance
“…Plasmids expressing the BirA*‐NE81 fusion were integrated in single or multicopy into the D. discoideum genome and high‐level fusion protein expression was induced by growth in axenic medium. Following purification of biotinylated proteins, immunoblotting revealed proximity labeling by BirA*‐NE81 of endogenous NE81, the lamin‐binding protein SUN1 , and the MAN1‐like protein Src1 . Additional proteins specifically biotinylated in the presence of BirA*‐NE81, but not in the control cells expressing BirA* alone, were also visualized in these experiments but as yet no analysis of these potentially novel interactors has been published.…”
Section: Bioid In Unicellular Organismsmentioning
confidence: 98%
“…Plasmids expressing the BirA*‐NE81 fusion were integrated in single or multicopy into the D. discoideum genome and high‐level fusion protein expression was induced by growth in axenic medium. Following purification of biotinylated proteins, immunoblotting revealed proximity labeling by BirA*‐NE81 of endogenous NE81, the lamin‐binding protein SUN1 , and the MAN1‐like protein Src1 . Additional proteins specifically biotinylated in the presence of BirA*‐NE81, but not in the control cells expressing BirA* alone, were also visualized in these experiments but as yet no analysis of these potentially novel interactors has been published.…”
Section: Bioid In Unicellular Organismsmentioning
confidence: 98%
“…As in metazoan lamins, an α-helical, central rod domain consisting of 370 amino acid residues is preceded by a head domain including Dictyostelium nuclear envelope 511 a CDK1 phosphorylation consensus sequence and followed by (in this order) a tail domain featuring a NLS, a conserved lamin tail domain, and a CaaX-box (= cysteine, two aliphatic aa and X = residue specifying the type of isoprene moiety) for prenylation at the C-terminal end (Krüger et al, 2012). Furthermore, microscopic and molecular studies confirmed that NE81 should be considered as a bona fide lamin due to its localization, functions, and protein interactions Batsios et al, 2016a;Batsios et al, 2016b;Grafe et al, 2019;Krüger et al, 2012). For example, immunogold-electron microscopy revealed an exclusive distribution of NE81 along the inner nuclear envelope.…”
Section: The Amoebozoan Laminmentioning
confidence: 94%
“…The latter represents the only LEMfamily protein in Dictyostelium (see below and Fig. 1) (Batsios et al, 2016b). Interactions between these protein families are conserved at least in amoebozoans and opisthokonts suggesting that they are very ancient and were possibly already a feature of the LECA.…”
Section: The Amoebozoan Laminmentioning
confidence: 98%
See 2 more Smart Citations